Favoritism of God? שָׁעָה in Genesis 4:1-16 and its implications for Cain’s status and offerings - Haezer Lisanias; Christopher James Luthy; Hanny Frederik; Yunus D. A. Laukapitang (Jurnal Jaffray, 2023)
This article aims to analyze the meaning of the word שָׁעָה based on Genesis 4:1-16 and explain its implications for the status of Cain and his offering. The research method used by the author in writing this is a qualitative research method based on hermeneutic principles. The results of this study indicate that the word שָׁעָה has the meaning of respect. God honoured Abel and his sacrifice. At the same time, God does not respect Cain and his gift. God knows what Cain's plot was before he killed Abel. The implication of Cain's status and sacrifice is that Cain's evil personality hindered him and his sacrifice before God. His person stands in the way of his gift to reach God.